2022
DOI: 10.3389/fmed.2022.1039707
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin and ezetimibe protect against hypercholesterolemia-induced lung oxidative stress, inflammation, and fibrosis in rats

Abstract: BackgroundHypercholesterolemia is a major risk factor for interstitial lung disease (ILD). Atorvastatin and ezetimibe are antilipemic drugs that have pleiotropic effects. However, their effects on pulmonary fibrosis prevention and the mechanisms underlying hypercholesterolemia have not been fully investigated. This study aimed to evaluate the individual effects of atorvastatin and ezetimibe on lung inflammation and fibrosis in high-cholesterol diet (HCD)-fed rats.Materials and methodsMale Sprague-Dawley rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…Lipid-lowering drugs have also attracted attention, and studies have shown that fenofibrate, pravastatin, atorvastatin, ezetimibe and probucol can significantly reduce the development of pulmonary fibrosis in animal models (see Table 1, Ref. [131][132][133][134][135][136][137][138][139]).…”
Section: Drugs Of Hypoglycemic or Lipid-lowering And Targeted Lipid-m...mentioning
confidence: 99%
“…Lipid-lowering drugs have also attracted attention, and studies have shown that fenofibrate, pravastatin, atorvastatin, ezetimibe and probucol can significantly reduce the development of pulmonary fibrosis in animal models (see Table 1, Ref. [131][132][133][134][135][136][137][138][139]).…”
Section: Drugs Of Hypoglycemic or Lipid-lowering And Targeted Lipid-m...mentioning
confidence: 99%